Préparer à évoluer dans un environnement professionnel multiculturel : l’(inter)culturel dans les manuels de spécialité affaires - Gajewska, Elżbieta (Neofilolog, 2023)
The article examines the ways intercultural aspects are dealt with in textbooks for learning business language (in the broad sense) in French, Spanish and Italian. The authors of the textbooks analyzed represent different approaches, both at the level of the declared learning objectives and at the level of the techniques applied. Among the textbooks analyzed there are also those oriented towards the development of intercultural skills. Their goal is not so much to prepare the learner to evolve in a given culture, but to make them aware of the differences between their own and the target culture(s)and to be able to mediate between the representatives of each of them. Although in a textbook for the teaching/learning of a foreign language for specialized purposes, intercultural training preparing for “culture shock” must necessarily be limited, the examples observed show that educators aware of the importance of this issue can offer interesting solutions and proposals.